Primary Intracranial Leiomyosarcoma- Report of a Rare Case with Literature Review (Bangladesh Journal of Neurosurgery, 2024)
A 29 years old man presented with a H/O headache and vomiting for 4 months, blurring of vision and gait ataxia for 2 months. A contrast MRI of brain indicated the lesion arose from the dura over left cerebellar hemisphere. A posterior fossa craniotomy was performed with a provisional diagnosis of meningioma. Histopathology and immunohistochemistry revealed Leiomyosarcoma. Further evaluation including Contrast CT and PET scan failed to identify any primary site. Primary intracranial leiomyosarcoma is very rare and only few cases were previously reported. The prognosis for primary intracranial leiomyosarcoma is poor with the longest reported survival being 32 months.Bang. J Neurosurgery 2023; 13(1): 48-50